2007
DOI: 10.1007/s10792-007-9072-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results of intravitreal triamcinolone acetonide injection for the treatment of diabetic macular edema

Abstract: In refractory diabetic macular edema, intravitreal triamcinolone effectively reduces foveal thickness and improves visual acuity in the short term, but with the extended follow-up, the number of recurrences and steroid-related complications were shown to increase. Nevertheless, it may be a therapeutic option in some patients that do not respond to previous laser photocoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
24

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
0
9
1
24
Order By: Relevance
“…Many authors [6][7][8][9][10] found that intravitreal injection of triamcinolone has a shortterm positive effect on diffuse and persisting DME after laser therapy, but its application leads to local complications like raised intraocular pressure and development of cataract [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [6][7][8][9][10] found that intravitreal injection of triamcinolone has a shortterm positive effect on diffuse and persisting DME after laser therapy, but its application leads to local complications like raised intraocular pressure and development of cataract [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Robert Machemer and colleagues in particular thought about intravitreal triamcinolone acetonide (IVTA) as a therapy of proliferative vitreoretinopathy [1,3,4,9,13,14,15,16]. As a consequence of Machemer’s suggestion, IVTA has been used for the treatment of other intraocular proliferative, edematous and neovascular diseases such as proliferative diabetic retinopathy [17,18], diffuse diabetic macular edema (DME) and diabetic retinopathy in general [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79], branch retinal vein occlusion (BRVO) [80,81,82,83,84,85,86,87,88,89,90,91,92], central retinal vein occlusion (CRVO) […”
Section: Introductionmentioning
confidence: 99%
“…A média de tratamentos foi de 2,6 no grupo tratado (n:34) e de 1,8 no grupo placebo (n:35). Outro estudo não controlado com dois anos de acompanhamento utilizando a dose de 4 mg intravítrea (40) , observou uma diferença significante da espessura macular central (OCT) entre o pré-tratamento e o 3º dia, 1º, 3º, 6º, 9º, 12º, 18º e 24º meses pós-aplicação (p<0,001). Porém, a acuidade visual média (logMAR) obteve melhora significante somente no 1º e 3º meses de acompanhamento (p<0,05), as visitas entre o 6º, 24º meses não obtiveram melhora significante da acuidade visual média (p>0,05).…”
Section: Discussionunclassified